Gender and citation in academic-scientific discourse: a systematic review - Esquivel Moreno, Lucero Itzel; Velásquez Upegui, Eva Patricia (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2024)
In recent years, the study of citations in academic-scientific discourse has made it possible to identify gender inequalities, since women’s research tend to be less recognized than men’s in many disciplines. However, there is some research that contradicts the aforementioned trends and affirms that there is no influence of gender in citation. The objective of this systematic review is to analyze articles in English and Spanish on citation, referred discourse and attribution, which have considered the gender variable in academic-scientific discourse. The period revised is from 1990 to 2022 and the Dialnet, Redalyc, Wiley and Google Scholar databases are used. As a result of the research, it is found that: 1) gender influences the citation in the academic-scientific discourse; 2) There is a lack of citation studies in Latin America, Oceania, Africa and Asia; 3) the largest number of studies have been produced from the disciplines of bibliometrics and scientometrics.